Diversity and Health: Two Sides of the Same Coin - Costa, Davide (Italian Sociological Review, 2023)
The globalization of contemporary society forces institutions to interact, in an ever-increasing way, with the concept of diversity. To date there is not a single definition, but the common element of the various notions concerns the particularity of the human in all its facets. The purpose of this paper is to analyze the relation between the concept of diversity and its relation to health. Diversity, in conclusion, becomes a challenge for any form of activity, both with research or with health implications. Above all, diversity presents itself as a challenge for the concrete and practical application of the paradigm of complexity.